Implementation of Traffic Safety Management on Road Sections with Non-Standard Grades - Juniar Perkasa Setia Laksana; Sabarudin; Raudha Hakim (PT FORMOSA CENDEKIA GLOBAL, 2022)
The majority of traffic accidents were caused by the negligence of drivers and road users, followed by vehicle factors, and road conditions as the following variable. The focus of this research is on traffic safety managementcaused by the level of incline and descent on the Sofi-Wayabula road, Morotai Regency. This quantitative descriptive research involved traffic management, maintenance, and patrol supervisors. The research instrument applied consisting observation sheets, interview, and documentation research sheets. The grade or road slope outside the standard requires the mitigation of traffic sign engineering. This study proposes it through the implementation of the Building Information Modeling or BIM method supported by the optimization of 3D animation of traffic signs, especially in North Maluku. The research findings indicated that a number of drivers were assisted by the implementation of 3D animation engineering of traffic signs at a number of accident-prone points along the 10.9 km on the Sofi-Wayabula road, Morotai Regency, North Maluku Province. The research targets agreed by the researcher were effective with traffic safety governance supported by renewable technology methods and engineering.